Navigating regulatory and analytical challenges in live biotherapeutic product development and manufacturing - , Microbiome Therapeutics Innovation Group; Barberio, Dana (Frontiers in Microbiomes, 2024)
The recent FDA approvals of Rebyota™ and Vowst™ represent landmark milestones within the burgeoning field of live microbiota-based products. Future microbiota-based treatment approaches also hold significant promise for treating patients with a myriad of diseases and disorders, yet substantial hurdles hinder their development and utilization. Foremost, existing regulatory frameworks governing live biotherapeutic product (LBP) manufacturing development have notable gaps, requiring comprehensive expansion and refinement. Along with regulatory challenges, hurdles remain in the optimization and validation of analytical methodologies essential for characterizing LBPs, including for microbial identification, potency, and bioburden. To address these challenges, Microbiome Therapeutics Innovation Group (MTIG) spearheaded collaborative efforts, engaging industry leaders and the FDA in discussions aimed at catalyzing improvements in LBP analytics and refining the current regulatory landscape. Extrapolating on feedback from these discussions, this review highlights challenges and identifies critical gaps. Specific recommendations for future regulatory guidance are proposed, as are recommendations for interactions that developers can take now with regulatory agencies to support the development of maturing guidance. Key analytical factors to consider in LBP development are reviewed, highlighting strengths and weaknesses of various methodologies. Collaboration among regulatory and government agencies, industry, and academia, facilitated by coalitions like MTIG, will be instrumental in ushering the microbiota-based therapeutics field into the next phase of approvals and advancements, ultimately benefiting patients.